"CEREMONIAL ROOMS" AT POTTERY MOUND, NEW MEXICO. (June 2014) - Ballagh, Jean H.; Phillips, David A.
Abstract : Excavations at Pottery Mound, a Pueblo IV site on the Rio Puerco south of Albuquerque, New Mexico, exposed three types of rooms: kivas, domestic rooms for both habitation and storage, and "ceremonial rooms." One of the last was sealed and contained ceremonial artifacts. Others were rooms whose internal features (and possibly also artifacts) differed from those of kivas and domestic rooms. The presence of "ceremonial rooms" at Pottery Mound may have to do with its probable multi-ethnic composition, or perhaps with the transformation of lineage-based to sodality-based ritual and social organization in the Eastern Pueblo world.